Study of waves observed in the equatorial ionospheric valley region using Jicamarca ISR and VIPIR ionosonde - Reyes, Pablo Martín (2017)
Incoherent scatter (IS) radar and ionosonde (VIPIR, vertical incidence pulsed ionospheric radar) data were taken concurrently at Jicamarca during campaigns of January, April, June, and July 2015, January 2016, and most recently April 2017 to bring more insight into the state and dynamics of the ionospheric E-F valley region and the 150-km radar echoes detected from this region. To better understand the rich and dynamic vertical structure of 150-km echoes observed at the Jicamarca Radio Observatory (JRO) and other equatorial stations and to contribute to the understanding of the physics of this region, we used JRO ISR and VIPIR ionosonde techniques to perform high spatial and temporal resolution measurements. We found correlations between VHF backscatter radar measurements and fluctuations detected with the VIPIR ionosonde, which is an indication of gravity waves playing a role in modulating the space-time structure of the 150-km echoes. Fluctuations with periods from 5 to 15 minutes are observed in VIPIR ionograms as well as in the layers found in the 50 MHz radar range-time-intensity (RTI) plots. The quiet-time stratified electron density contours are being rippled by waves propagating through the ionosphere. Evidence for this is the fluctuation of virtual reflection heights and angle of arrival (AOA) of the ionosonde echoes. The AOA is provided by interferometry, which indicates that the echo is not always coming from overhead. Scatter plots of the AOA in the receiving antenna’s orthogonal baselines give us the propagation direction. Plots of virtual height and AOA obtained using VIPIR data show phase fronts propagating downwards, which is characteristic of internal gravity waves (IGW). Other characteristics of IGW are present in the oscillations of virtual height: their frequencies are just below the Brunt-Väisälä frequency, their amplitudes increase with altitude, and shorter vertical wavelengths seen in lower altitudes are heavily damped in higher altitudes. The observed IGW exhibit fluctuations similar to those seen in the thin “forbidden” or “quite” zone of the 150-km echo undulations, which indicates some IGW-driven modulations of the 150-km echo as has been suggested previously [e.g. Kudeki and Fawcett, 1993; Chau and Kudeki, 2013]. Phase profiles of cross- correlation pair of antennas in the IS Faraday rotation experiment exhibit a smooth progression with altitude. That means that there are no sharp density gradients that could be a source of plasma instabilities. Still, density variations across the magnetized plasma in the region can be key to explaining the enhanced echoes observed via the electrodynamics that they can drive. We also found that there exist sub-minute quasi-periodic (SMQP) fluctuations when zooming into high time resolution RTI plots. This is a new observation that has not been reported in the literature to date. A method was designed in order to validate the existence of SMQP fluctuations. The method consisted of identifying episodes of sub-minute fluctuations in a non-exhaustive search of high resolution RTI plots using a web-based interactive tool designed for zooming in and marking the episodes where the sub-minute period fluctuations were found. We found a wide range of sub-minute periods, with a predominance between 15 and 20 seconds. This was a first step towards reporting SMQP; a more exhaustive method to search for these fluctuations is being produced. This multi-instrument approach helps us to characterize the daytime electron density fluctuations in the equatorial valley region, and aims to contribute to the goal of understanding better the fundamental physics of the region.